REPEAT BREEDER PADA SAPI KRUI DI KECAMATAN PESISIR SELATAN KABUPATEN PESISIR BARAT - Luluk Adria Ningrum; Madi Hartono; Sri Suharyati; Siswanto Siswanto (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2020)
Research on repeat breeder in Krui Cattle in Pesisir Selatan District of Pesisir Barat Regency was held on 23 December 2019 until 15 January 2020 with 2 inseminators, 166 Krui Cattles belong to 75 farmers. The purpose of this research were to know: 1) the value of repeat breeder in Krui Cattle in Pesisir Selatan District of Pesisir Barat Regency, and 2) the factors and the magnitude of the factors which disturb repeat breeder of Krui cattle in Pesisir Selatan District of Pesisir Barat Regency. Data was analysed by logistic regression using SPSS (Statistics Package for Social Science) program. The result showed that repeat breeder of Krui cattle in Pesisir Selatan District of Pesisir Barat Regency was 10,24%. Factors that affect the repeat breeder were farmers education that negatively associated with factor value of 5,757; the location of the cage from the farmers house that positively associated with factor value of 0.090; and age of first mating that negatively associated with factor value 1,088. Keywords: Affecting Factors, Krui cattle, Magnitude factors, Pesisir Selatan, Repeat breeder